x(x+1)-2(x+1)=

Simple and best practice solution for x(x+1)-2(x+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+1)-2(x+1)= equation:


Simplifying
x(x + 1) + -2(x + 1) = 0

Reorder the terms:
x(1 + x) + -2(x + 1) = 0
(1 * x + x * x) + -2(x + 1) = 0
(1x + x2) + -2(x + 1) = 0

Reorder the terms:
1x + x2 + -2(1 + x) = 0
1x + x2 + (1 * -2 + x * -2) = 0
1x + x2 + (-2 + -2x) = 0

Reorder the terms:
-2 + 1x + -2x + x2 = 0

Combine like terms: 1x + -2x = -1x
-2 + -1x + x2 = 0

Solving
-2 + -1x + x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-1 + -1x)(2 + -1x) = 0

Subproblem 1

Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1

Subproblem 2

Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2

Solution

x = {-1, 2}

See similar equations:

| 5(2x+6)=10x+30 | | 5(0)+4y=0 | | 3x+0.8x=90 | | x^2+2x+7x+14=0 | | x^4-7x^3-6x^2= | | -3b+6=-4b-10 | | 5x+9+2x=23 | | 3x^2-8x+7=0 | | 3.5=3.5+0.076x | | 4.5x-5.4=2.7x | | 5x+4(-4)=0 | | 4=p+2 | | x-2=6-3x | | x-5y=12 | | 2p=10.2 | | 3(2x+5)=6x+5 | | 5-(x+3)=-x+2 | | 12.85=y+4 | | -4x+(-1)=5 | | c-1.86=6.7 | | 3a^2-13a=-14 | | -4x+1=5 | | q-3=1 | | -4-0=5 | | y+9.59=19.59 | | 12x+11=10x+17 | | 6x-9=6(x-6) | | -4x+0=5 | | 2(4x-1)=8x-2 | | 0.6x+4=0.2x+5 | | 5x+9=x+69 | | 3(2x+2)+5x=2(4x-1)-2(-x+1) |

Equations solver categories